2011
DOI: 10.1111/j.1743-498x.2010.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a focused ultrasound training programme for medical undergraduate students

Abstract: We have shown for the first time that it is feasible to train inexperienced undergraduate students to scan the abdominal aorta to a professional standard using a focused training course. It is time for the medical education community to address whether focused ultrasound training should accompany traditional clinical skills, such as using a stethoscope, in UK medical school curricula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 9 publications
1
77
0
1
Order By: Relevance
“…Dinh et al [46] found that students that had ultrasound incorporated into their physical examination curriculum obtained greater OSCE scores than a cohort of students that took the exams prior to the introduction of ultrasound, in the same medical school. The educational interventions found here range from those that teach students to scan a wide range of anatomy [47,48] or regional anatomy [49] to more focused exams of the vascular [50][51][52], abdominal [53][54][55], head and neck [56], cardiac [57,58] and respiratory [59] systems. Some institutions taught students ultrasound-specific protocols such as FAST [60][61][62] or USEFUL [63] scans.…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…Dinh et al [46] found that students that had ultrasound incorporated into their physical examination curriculum obtained greater OSCE scores than a cohort of students that took the exams prior to the introduction of ultrasound, in the same medical school. The educational interventions found here range from those that teach students to scan a wide range of anatomy [47,48] or regional anatomy [49] to more focused exams of the vascular [50][51][52], abdominal [53][54][55], head and neck [56], cardiac [57,58] and respiratory [59] systems. Some institutions taught students ultrasound-specific protocols such as FAST [60][61][62] or USEFUL [63] scans.…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…Moreover, the development of fully capable, small-sized portable ultrasounds represents an important technological advance that may aid its use in community-level contexts or acute care centers in resource-limited settings. Similarly, training of diagnostic ultrasound to clinicians with a course involving theoretical and practical training, and ongoing mentoring with postcourse supervision and accreditation may provide a high standard of practice [26][27][28]. We sought to characterize agreement between WHO algorithm for pneumonia with lung consolidation identified by point-of-care ultrasound and to determine the feasibility of point-of-care ultrasound in resource-limited settings for the diagnosis of childhood pneumonia by trained general health practitioners following a 7-day standardized training course.…”
Section: Introductionmentioning
confidence: 99%
“…62 While OSCEs have limited use in procedural training, standardized patients have been used for noninvasive nonpainful procedural training and assessment such as ultrasound. OSCEs have been used to evaluate ultrasonography of the abdominal aorta, 63 as well as the completion of the Focused Assessment with Sonography in Trauma examination. 59 In many of these circumstances the OSCE is used to evaluate the effectiveness of an educational intervention, either through comparison of pre-and posttesting or through comparison of study and control groups.…”
Section: Overview Of Assessment Methods Identifiedmentioning
confidence: 99%